Transforming sanitation coverage: civic champions inspire sustainable change in Cambodia - Lyn McLennan; Mai Sieng; D. Phav (2014)
Inspired by local leaders who have motivated their communities to make transformational change in sanitation coverage, WaterSHED is implementing a proof-of-concept leadership development project. Self-selected participants from two ‘treatment’ districts in rural Cambodia are engaged in a cyclical program of conferencing and coaching. Transformational change is rewarded through a combination of output-based financial and non-financial incentives. Significant improvement in sanitation coverage, including villages with 100 percent sanitation access is targeted. We are evaluating the effectiveness of the methodology to catalyze civic champions to enable more rapid and cost-effective means to reach total sanitation. Among other indicators, we are measuring the number of latrines sold, using neighboring (non-treatment) districts as reference points for comparison. Qualitative transformation is captured, through the mentoring program, documentary videos and small case studies. Early indications are that the enabling civic officials to enhance their leadership capacity, is cost-effective, sustainable and applicable beyond sanitation.